Radiation Leakage Images For Two Different Dielectric-Loaded Surface Plasmon Polariton Waveguides (Bulletin of Pure and Applied Sciences – Physics, 2022)
We have studied about leakage radiation images obtained for two different  dielectric-loaded surface plasmon polariton waveguides based on routing structures;  linear couplers and bent waveguides. By simultaneously imaging the conjugated  aperture and field planes of the microscope, we unambiguously quantify the  degeneracy lift occurring for strongly interacting dielectric loaded surface plasmon  polariton waveguides and visualize the symmetry of the coupled modes. We have  obtained the wave vector distribution and showed its evolution with the bend  radius. We have developed a numerical and an analytical analysis for momentum  distribution. We have found that for large radii i.e. for vanishing bending loss, we  can link the plasmon in Fourier space with the geometrical and modal properties of  the bend structure. It was also found that the radial dependence of the wave vector  distribution is governed by the phase difference. The obtained results were found in  good agreement with previously obtained results.